Pharmacological characterization of soluble and membrane anchored agonists of formyl peptide receptors. - Zhang, Naixin. (2017)
Abstract: Formyl peptide receptors (FPRs) are a family of G protein-coupled receptors found on monocytes, polymorphonuclear leukocytes, dendritic cells, macrophages, and in other tissues. FPRs have been shown to have a putative role in both the acute inflammatory response and chronic inflammation. WKYMVM and its D-enantiomer WKYKVm (W-peptides) are a pair of synthetic hexapeptides that are promiscuous agonists of FPRs. Previous studies have shown that WKYMVm has anti-inflammatory and proresolving effects via activation of the formyl peptide receptor subtype, FPR2. Since both peptides have short half-lives, in order to develop peptide analogs as a potential therapeutic, more stable and long-acting analogs are needed. In this paper, an established MTL/SMAL strategy was used to generate novel lipidated analogs of WKYMVM and WKYMVm. Both lipidated peptides exhibited enhanced potency and wash-resistance in cell based assays. The two peptides also showed a potency shift in the presence of albumin, suggesting adherence to albumin. This is an important property which has previously been shown to enhance the in vivo half-life of other lipidated peptides. The current study describes a practical way in which the potency of both W-peptide enantiomers were enhanced using lipidation, a strategy which may extend the half-life of the ligands. In summary, we have successfully converted W-peptides into more promising therapeutic candidates which can be subsequently tested as modulators of FPR2 in vivo.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisor: Alan Kopin.; Committee: Alan Kopin, and Martin Beinborn.; Keyword: Pharmacology.